Predator‐specific inducible morphological defenses of a water flea against two freshwater predators. (25th April 2020) - Ritschar, Sven; Rabus, Max; Laforsch, Christian
Abstract: The expression of inducible morphological defenses in Daphnia in response to a single predator is a well‐known phenomenon. However, predator‐specific modifications of the same defensive traits as an adaption to different predator regimes is so far only described for Daphnia barbata . It is unknown if this accounts only for this species or if it is a more widespread, general adaptive response in the genus Daphnia . In the present study, we therefore investigated whether a clone of the pond‐dwelling species Daphnia similis responds to different predatory invertebrates ( Triops cancriformis ; Notonecta maculata ) with the expression of predator‐specific modifications of the same defensive traits. We showed that Triops‐ exposed individuals express a significantly longer tail‐spine, while body width decreased in comparison to control individuals. Additionally, they also expressed inconspicuous defenses, that is, significantly longer spinules on the dorsal ridge. The Notonecta ‐exposed D. similis showed a significantly longer tail‐spine, longer spinules and a larger spinules bearing area on the dorsal ridge than control individuals as well. However, a geometric morphometric analysis of the head shape revealed significant, predator‐specific changes. Triops ‐exposed individuals expressed a flattened head shape with a pronounced dorsal edge, while Notonecta ‐exposed individuals developed a high and strongly rounded head. Our study describes so far unrecognized inducible defenses of D. similis against two predators in temporary waters. Furthermore, the predator‐dependent change in head shape is in concordance with the 'concept of modality', which highlights the qualitative aspect of natural selection caused by predators. Abstract : Shape variation in the analysed datasets. Each row represents a shape variation described by a specific principle component. Mean: The mean head shape of the analysed shape difference in the data set, next to it are the shapes −2 SD and +2 SD representing the broadness of shape variance within the data sample. All: Overlay of the three outputs on the right. The mean is highlighted in orange. Black lines indicate the described shape variance. Black Arrows: Indicate the area where the PC describes the shape variation. Control versus Triops : Comparison of the head shape of Triops ‐exposed and non‐exposed D. similis . PC1 and PC2 were chosen, since both individually contribute to specific shape differences of the head between the compared groups. Thereby, PC1 describes the differences of the shape of the dorsal part of the head between the Triops ‐exposed and non‐exposed D. similis . PC2 covers the differences of shape of the rostral part of the head between the Triops ‐exposed and non‐exposed D. similis . Control versus Notonecta : Comparison of the head shape of Notonecta ‐exposed and non‐exposed D. similis . Only one PC1 was chosen, since it covers the main shape alteration between the compared groups. Thereby, the PC describes the differences in overall rounding and height of the head between the Notonecta ‐exposed and non‐exposed D. similis . Triops versus Notonecta : Comparison of the head shape of Triops ‐exposed and Notonecta ‐exposed D. similis . Only one PC1 was chosen, since it covers the main shape alteration between the compared groups. Thereby, PC1 describes the differences in overall rounding of the head between the Notonecta ‐ and Triops ‐exposed D. similis .